2009
DOI: 10.4049/jimmunol.0901422
|View full text |Cite
|
Sign up to set email alerts
|

Limited Role of CD4+Foxp3+ Regulatory T Cells in the Control of Experimental Cerebral Malaria

Abstract: Cerebral malaria (CM) associated with Plasmodium berghei ANKA (PbA) infection is an accepted model of human CM. CM during PbA infection critically depends on sequestration of T cells into the brain. Several studies aimed to address the role of regulatory T cells (Treg) in modulating this pathogenic T cell response. However, these studies are principally hampered due to the fact that until recently no reagents were available to deplete Foxp3+ Treg specifically. To study the function of Treg in the genesis of CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 38 publications
4
43
2
1
Order By: Relevance
“…For example, it was reported that Treg cells induced in vivo by IL-2/anti-IL-2 complexes in P. berghei infected mice protected the mice from neurological disease [9]. A study by Steeg et al [11] showed that selective depletion of CD4 + Foxp3 + cells had no apparent effect on CM development in P. berghei infection. In this study, we also evaluate the role of CD4 + CD25 + Treg cells in regulation of CM development.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, it was reported that Treg cells induced in vivo by IL-2/anti-IL-2 complexes in P. berghei infected mice protected the mice from neurological disease [9]. A study by Steeg et al [11] showed that selective depletion of CD4 + Foxp3 + cells had no apparent effect on CM development in P. berghei infection. In this study, we also evaluate the role of CD4 + CD25 + Treg cells in regulation of CM development.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the role of Treg cells, defined either by CD4 + CD25 + or CD4 + Foxp3 + , in regulation of CM in murine malaria model, but inconsistent finding are reported [9,11,22,23]. To address this question, we performed experiment to determine the role of Treg cells, in parallel with Breg cells, in control of CM in P. berghei infected mice.…”
Section: Role Of Cd4 + Cd25 + Treg Cells In Protection From CM In P mentioning
confidence: 99%
See 2 more Smart Citations
“…Regulatory T cells can be beneficial or detrimental to the induction of ECM depending on the method and timing of regulatory T cell depletion and the genetic background of the host (17)(18)(19)(20)(21)(22)(23)(24). Th17 cells, which induce tissue inflammation and are capable of disrupting the blood brain barrier (25), do not appear to contribute to the pathogenesis of ECM (26).…”
Section: Erebral Malaria (Cm) Remains a Major Cause Of Death Inmentioning
confidence: 99%